Edukasi mitigasi bencana gunung meletus di wilayah BPBD Klaten: Edukasi mitigasi bencana gunung meletus di wilayah BPBD Klaten - Ida Nur Imamah; Fida’ Husain; Nur Tjahjono Suharto; Didik Iman Margatot (Yayasan Inspirasi El Burhani, 2023)
Background:Indonesia is a country crossed by the equator which has various kinds of potential natural beauty such as beaches, lakes, caves, waterfalls, mountains and others. On the island of Java there are 35 volcanoes,Mount Merapi is one of the most active volcanoes in Indonesia and even in the world. Efforts to reduce disaster risk are carried out before a disaster occurs,which is called risk management, while after a disaster occurs,it is called impact management. The results of disaster mitigation efforts are used for the disaster preparedness process.Objective:Education is carried out to increase knowledge of the community, especially in communities that are in areas prone to the Mount Merapi disaster.Method:Community service is carried out using educational video media which is given to communities that are vulnerable to being affected by Mount Merapi.Result:The results of the student pretest showed that 70% of the participants did not understand about volcanic eruption mitigation and 30% of the students already understood. The posttest was carried out with the same questions as the pretest and the results showed that 93% students already understood the issue. explanation of mitigation for the volcanic eruption disaster.Conclusion:There is an increase in knowledge after disaster mitigation education is carried out.